Root hair growth from the pH point of view - Stéger, Anett; Palmgren, Michael (Frontiers in Plant Science, 2022)
Root hairs are tubular outgrowths of epidermal cells that increase the root surface area and thereby make the root more efficient at absorbing water and nutrients. Their expansion is limited to the root hair apex, where growth is reported to take place in a pulsating manner. These growth pulses coincide with oscillations of the apoplastic and cytosolic pH in a similar way as has been reported for pollen tubes. Likewise, the concentrations of apoplastic reactive oxygen species (ROS) and cytoplasmic Ca2+ oscillate with the same periodicity as growth. Whereas ROS appear to control cell wall extensibility and opening of Ca2+ channels, the role of protons as a growth signal in root hairs is less clear and may differ from that in pollen tubes where plasma membrane H+-ATPases have been shown to sustain growth. In this review, we outline our current understanding of how pH contributes to root hair development.